Effects of Hsp90 Inhibitor Ganetespib on Inhibition of Azole-Resistant Candida albicans - Yuan, Rui; Tu, Jie; Sheng, Chunquan; Chen, Xi; Liu, Na (Frontiers in Microbiology, 2021)
Candida albicans is the most common fungi pathogen. Recently, drug resistance of Candida albicans is increasingly severe. Hsp90 is a promising antifungal target to overcome this problem. To evaluate the effects of Hsp90 inhibitor ganetespib on inhibiting azoles-resistant Candida albicans, the microdilution checkerboard method was used to measure the in vitro synergistic efficacy of ganetespib. Fluorescence polarization assay was conducted to detect the Hsp90 inhibitory activity. The XTT/Menadione reduction, microscopic observation, and Rh6G efflux assay were established to investigate the effects of ganetespib on azoles-resistant Candida albicans biofilm formation, filamentation and efflux pump. Real-Time RT-PCR Analysis and Flow Cytometry were employed to clarify the mechanism of antagonizing drug-resistance. The in vivo antifungal efficacy of ganetespib was determined by the infectious model of azole-resistant Candida albicans. Ganetespib showed excellent synergistic antifungal activity in vitro, and significantly inhibited the fungal biofilm formation, whereas had no inhibitory effect on fungal hypha formation. Expression of azoles target enzyme gene ERG11 and efflux pump genes CDR1, CDR2 and MDR1 were significantly down-regulated when ganetespib was used in combination with FLC. In a mouse model infected with FLC-resistant Candida albicans, the combination of ganetespib and FLC effectively reversed the FLC resistance and significantly decreased the kidney fungi load of mouse.